Nexos entre México y Europa Centro-Oriental - Szente-Varga, Mónika (Acta Hispanica, 2012)
The first diplomatic and consular relations were established between Mexico and the Habsburg Empire in the 1800 s, motivated basically by commerdal reasons and dynastic interests. These got to an abrupt end with the execution of Emperor Maximilian in Querétaro in 1867, and diplomatic relations were resumed only decades later, in 1901, which is, in fact, our starting point. This essay examines the development of diplomatic relations between Mexico and Central-Eastern Europe from the beginning of the 20’’ centuiy until nowadays. It is divided into chronological chapters, where we study bilateral relations in the coordinates of the following periods: beginning of the century, the period between the two world wars, the Second World War, Cold War and recent years. The investigation in based on documents of the Ministry of Foreign Affairs of Mexico (SRE-AHD) and of the Hungarian National Archive (MOL).